2019
DOI: 10.1021/acs.est.9b00491
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Combinations of Water Treatment Processes on the Concentration of Disinfection Byproducts and Their Precursors in Swimming Pool Water

Abstract: To mitigate microbial activity in swimming pools and to ensure hygienic safety for bathers, pool systems have a recirculating water system ensuring continuous water treatment and disinfection by chlorination. A major drawback associated with the use of chlorine as disinfectant is its potential to react with precursor substances present in pool water to form harmful disinfection byproducts (DBPs). In this study, different combinations of conventional and advanced treatment processes were applied to lower the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Their use for irrigating green areas, Water Policy Vol 00 No 0, 11 sprinkling grounds and tennis courts (very often located near a swimming pool), as well as flushing toilets is an easy solution that allows to dramatically reduce the environmental and economic costs (Wyczarska-Kokot, 2016). For instance, just filtering through granular activated carbon removes efficiently free chlorine and DBPs from the water, enabling its use in toilet flushing and other low-level applications (Skibinski et al, 2019). Advance membrane filtration technology, including micro-, ultra-and nanofiltration, offers better outcomes when applied to backwashing waters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their use for irrigating green areas, Water Policy Vol 00 No 0, 11 sprinkling grounds and tennis courts (very often located near a swimming pool), as well as flushing toilets is an easy solution that allows to dramatically reduce the environmental and economic costs (Wyczarska-Kokot, 2016). For instance, just filtering through granular activated carbon removes efficiently free chlorine and DBPs from the water, enabling its use in toilet flushing and other low-level applications (Skibinski et al, 2019). Advance membrane filtration technology, including micro-, ultra-and nanofiltration, offers better outcomes when applied to backwashing waters.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional or traditional water treatment includes sedimentation, coagulation, sand and granular activated carbon filtration. Advanced procedures like membrane filtration (micro-, nano-or ultrafiltration) or ultraviolet irradiation are increasingly used for pool water treatment (Skibinski et al, 2016(Skibinski et al, , 2019. Simple purification processes, including a settling tank with a coagulant chamber and after a tank for intensive aeration, allow the backwash water to introduce into waters or the ground (Wyczarska-Kokot & Lempart, 2018).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine has a massive chloroform DBP formation potential (Berg et al, 2019) which is likely to end up in the pool's air (Berg et al, 2019). In addition, results have shown that removing the volatile DBP trichloramine across the water treatment train is not a feasible strategy due to the high formation rate in the pool (Skibinski et al, 2019). Thus, the ventilation concept and fresh air supply for the facility are crucial to reduce the negative health impacts for the occupants.…”
Section: Apply Better Disinfection Methodsmentioning
confidence: 99%
“…The swimming facility at Jøa is a state-of-the-art swimming facility which complies with the Norwegian passive house standard [22]. It includes a ventilation heat recovery system equipped with a heat pump, as recommended in the literature [5,43], and conventional water treatment, which research has found to be the most effective water treatment train [44].…”
Section: The Technical Systemsmentioning
confidence: 99%